PET Imaging of Neutrophils Infiltration in Alzheimer's Disease Transgenic Mice - Kong, Yanyan; Liu, Kawai; Hua, Tao; Zhang, Chencheng; Sun, Bomin; Guan, Yihui (Frontiers in Neurology, 2020)
Introduction: Neutrophils play a critical role in the innate immune system. Neutrophil hyperactivation has been identified as a biomarker of Alzheimer’s disease (AD). However, there is still no in vivo imaging tool to study the neutrophils infiltration in AD dynamically. 68Ga-PEG-cFLFLFK, an antagonist of the neutrophil formyl peptide receptor (FPR) with a high binding affinity, has been developed as a specific tracer to probe the activation of neutrophils. In this study, we aim to detect the variation and mechanism of neutrophil infiltration in the AD transgenic mice. Methods: In this study, we used the B6;129-Psen1tm1Mpm Tg(APPSwe,tauP301L)1Lfa/Mmjax mouse model, which was confirmed by RT-PCR. Open field test, morris water maze, high plus maze and Y-maze test were performed to evaluate the status of the mice. 18F-AV45, 18F-PM-PBB3, 68Ga-PEG-cFLFLFK and 18F-DPA714 was synthesized by the previously reported. Serial microPET was used to investigate the uptake of tracer in the AD transgenic mice and control at different ages. Western blot was used to investigate the expression of different proteins in each group. Results: We have proved the successful establishment of transgenic models by RT-PCR, behavior tests, 18F-AV45 and 18F-PM-PBB3 PET imaging. We also found the increased neutrophils infiltration in the brain of transgenic models through 68Ga-PEG-cFLFLFK and western blots. Furthermore, our studies demonstrated elevated CAP37, which is produced by neutrophils, promoted the expression of Iba1, iNOS and COX in the cultured microglia. 18F-DPA714 PET imaging studies proved the raised activated microglia in the brain of transgenic models. Conclusions: These results indicated that increased neutrophil infiltration in the heart and brain of AD mice. 68Ga-PEG-cFLFLFK PET imaging is a sensitive approach for studying the status and mechanism of neutrophil on AD. Infiltrated neutrophils induced activation of microglia by CAP 37 secretion.